Podemos et le 15-M : de l’indignation au gouvernement de coalition (2011-2021) - Mathieu Petithomme (Cahiers de Civilisation Espagnole Contemporaine)
This article questions the links between Podemos and the Indignados movement, by wondering to what extent this party founded in 2014 can be considered as “the party of the Indignados”. It stresses the similarities between the 15-M, an unprecedented social movement of indignation among the youth, with Podemos, whose initial objective was to give a political outlet to the new social demands politicized by the 15-M : fight against corruption, transparency, participation and direct democracy demands, end of austerity policies. But it also shows that, by becoming institutionalized within the political game, Podemos has normalized and moved away from the original ideals of the 15-M, arousing in return a form of militant disillusion. He nevertheless has the merit, ten years after the 15-M, for having succeeded in forming the first coalition of the lefts since the Second Republic.